Simulation of air foil bearings for use in turbo compressor applications. (15th June 2023) - Heaps, William; Questa, Harry; Mohammadpour, Mahdi; Bewsher, Stephen R.; Offner, Guenter
This paper explores the use of air foil bearings (AFBs) in turbo compressor applications. AFBs are characterised by their high speed and clean operation exhibiting low mechanical losses and presenting the potential use in hydrogen fuel cell applications, as the problem of membrane poisoning is avoided. A novel explicit co-simulation methodology for analysing the dynamic performance of a turbocharger using AFBs is presented. Using bearing maps defining collinear stiffness and damping, an adaptable tool is created through a mathematical bearing model explicitly coupled with a flexible multi-body dynamic system. This system level model considers flexibility of the bodies contained, as well as a Coulomb damping mechanism provided by the sub-foil structure in the AFBs. The resonance of the system was observed around 70 krpm with nonlinear and sub synchronous vibrations also being experienced. Although computationally intensive, significantly more modes of vibration were detected when compared to rigid body analysis.